Substituent‐Controlled Divergent Cascade Cycloaddition Reactions of Chalcones and Arylalkynols: Access to Spiroketals and Oxa‐Bridged Fused Heterocycles. Issue 16 (6th July 2021) - Zeng, Tianlong; Kong, Jingyang; Wang, Hongkai; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract: Herein, we report substituent‐controlled divergent cascade cycloaddition reactions of chalcones and arylalkynols in the presence of PtI2 . Depending on the substituent on the chalcone, either spiroketals or oxa ‐bridged fused heterocycles could be obtained in the ranges of 86–97% and 87–95% yields under identical reaction conditions. Control experiments were carried out to elucidate the origin of the high chemoselectivity. These provide a method for the synthesis of a diverse array of structurally complex oxygen‐containing heterocycles. Abstract :